Abemaciclib: a CDK4/6 inhibitor for the treatment of HR+/HER2– advanced breast cancer - Corona SP; Generali D (Dove Medical Press, 2018)
Silvia Paola Corona,1 Daniele Generali2 1Radiation Oncology Department, Peter MacCallum Cancer Centre, Bentleigh East, VIC, Australia; 2Department of Medical, Surgery and Health Sciences, University of Trieste, Trieste, Italy Abstract: Although early breast cancer (BC) is highly curable, advanced or metastatic disease poses numerous challenges in terms of medical management and treatment decisions and is associated with significantly worse prognosis. Among the new targeted agents, anticancer drugs exploiting the cell-cycle machinery have shown great potential in preclinical studies. CDK4/6 inhibitors target the cyclin D/CDK/retinoblastoma signaling pathway, inducing cell-cycle arrest, reduced cell viability and tumor shrinking. As the cyclin D/CDK complex is activated downstream of estrogen signaling, the combination of CDK4/6 inhibitors with standard endocrine therapies represents a rational approach to elicit synergic antitumor activity in hormone receptor-positive BC. The results of clinical trials have indeed confirmed the superiority of the combination of CDK4/6 inhibitors plus endocrine therapies over endocrine therapy alone. Currently approved are three compounds that exhibit similar structural characteristics as well as biological and clinical activities. Abemaciclib is the latest CDK4/6 inhibitor approved by the US Food and Drug Administration (FDA) in view of the results of the MONARCH 1 and 2 trials. Further trials are ongoing as other important questions await response. In this review, we focus on abemaciclib to examine preclinical and clinical results, describing current therapeutic indications, open questions and ongoing clinical trials. Keywords: CDK4/6 inhibitor, abemaciclib, breast cancer, hormone receptor-positive BC, metastatic BC, mBC